2022
DOI: 10.3390/microorganisms10101924
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Biofilm-Forming Microbial Communities in Fermentative Biohydrogen Process: An Overview

Abstract: Amongst the biofuels described in the literature, biohydrogen has gained heightened attention over the past decade due to its remarkable properties. Biohydrogen is a renewable form of H2 that can be produced under ambient conditions and at a low cost from biomass residues. Innovative approaches are continuously being applied to overcome the low process yields and pave the way for its scalability. Since the process primarily depends on the biohydrogen-producing bacteria, there is a need to acquire in-depth know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…); however, most studies coincide with these results, as shown in similar studies conducted in other regions such as Asia [ 41 , 42 ], Europe [ 43 ], Africa [ 44 ], and North and South America [ 45 ]. From a techno-economic standpoint, fruit and vegetable wastes are deemed suitable for SCP due to their high composition of monomeric sugars (glucose and sucrose), low lignin content, biodegradable nature, ability to be assimilated by a wide spectrum of microorganisms, and high accessibility [ 46 , 47 ]. It has also been shown that fruit wastes such as pineapple peel, orange peel, potato peel, banana peel, and carrot pulp increase the SCP yields due to their high composition of sugars that ranges from 54.17 to 83% [ 48 , 49 ].…”
Section: Nutritional Composition Of Food Waste and Its Suitability Fo...mentioning
confidence: 99%
“…); however, most studies coincide with these results, as shown in similar studies conducted in other regions such as Asia [ 41 , 42 ], Europe [ 43 ], Africa [ 44 ], and North and South America [ 45 ]. From a techno-economic standpoint, fruit and vegetable wastes are deemed suitable for SCP due to their high composition of monomeric sugars (glucose and sucrose), low lignin content, biodegradable nature, ability to be assimilated by a wide spectrum of microorganisms, and high accessibility [ 46 , 47 ]. It has also been shown that fruit wastes such as pineapple peel, orange peel, potato peel, banana peel, and carrot pulp increase the SCP yields due to their high composition of sugars that ranges from 54.17 to 83% [ 48 , 49 ].…”
Section: Nutritional Composition Of Food Waste and Its Suitability Fo...mentioning
confidence: 99%
“…The loosening of the lignocellulosic structure enhances the dark fermentative bacteria's ability to undergo dark fermentation to maximize biogas production [77]. Hydrogen-producing bacteria require optimum operational conditions such as pH value, temperature, and total solids concentration to enhance the dark fermentation [78][79][80][81][82] of GRH. The optimum pH value used in this dark fermentation was 5.5.…”
Section: Biogas and Hydrogen Production From Pretreated Grhmentioning
confidence: 99%